Preparation and characterization of 49% methyl-grafted natural rubberbased polymer gel electrolytes for proton batteries / Ainnur Sherene Kamisan - Kamisan, Ainnur Sherene (2011)
This thesis focuses on the preparation and characterization of liquid electrolytes (LEs), polymer gel electrolytes (PGEs), and composite polymer gel electrolytes (CPGEs). LEs were first prepared by dissolving ammonium triflate (NH4CF3SO3) in propylene carbonate (PC) using various molar concentrations of NH4CF3SO3. The optimum conductivity (0.7 M) of the liquid electrolyte (LE) was then gelled with different concentrations of MG49. The conductivity of PGE measured by electrical impedance spectroscopy (EIS) showed a noteworthy increase by one order (approximately 10" S cm"1) when 3 wt.% MG49 was incorporated into 0.7 M of the LE. This phenomenon is best clarified by the breathing polymeric chain model. Although PGE has a high conductivity (1.23 x 10" S cm"), its physical properties need to be improved for practical application. Therefore, the PGE was dispersed with SiC>2 and AI2O3 to obtain CPGEs. The plot of log a versus 1000/T for all systems implies that the systems follow the Arrhenius rule, in which conductivity is thermally assisted. ATR-FTIR spectroscopy was used to study the interaction between components. The changes in band vibration are observable primarily due to the interaction between the C=0 of MG49 and NH4+ of ammonium triflate. An Ubbelohde viscometer was used to measure the viscosity of all systems, which is the only physical property discussed in the current thesis. PGE filled with 8 wt.% of SiC>2 and 7 wt.% of AI2O3 which are the highest conductivities of CPGE were chosen to fabricate a proton battery with the cell configuration of Zn || CPGE || Mn02- The OCV and discharge characteristics of both cells were studied and compared. The CPGE cell with SiC>2 filler (Cell A) was the superior in all aspects because of its higher CPGE conductivity (7.55 x 10"3 S cm"1) compared to Cell B (6.75 x 10'3 S cm"1). Cell A stabilized at 1.49 V under an open cell condition, with discharge capacity of 17.85 mAh at a 0.5 mA current drain. Cell A also had the specific power and specific energy of 0.75 W Kg"1 and 26.78 Wh Kg"1, respectively, at a 0.5 mA current drain.